Relationship between Resilience and Social and Organizational Support among Nurses Working with COVID-19 Patients: A Cross-Sectional Study - Soudabeh Mehdizadeh; Phateme Aghamohammadi; Maryam Maleki; Masoumeh Hasanlo; Soheila Abbasi (Wolters Kluwer Medknow Publications, 2024)
Background: One of the coping strategies in stressful situations effectively is resilience skills. Due to the coronavirus disease 2019 (COVID-19) pandemic and its resulting stresses, this study was conducted to determine the relationship between resilience and social and organizational support among nurses working with COVID-19 patients. Materials and Methods: A cross-sectional study was undertaken on 224 nurses working with COVID-19 patients in Iran in 2021. A demographic questionnaire, the Connor-Davidson Resilience Scale, Multidimensional Scale of Perceived Social Support, and Survey of Perceived Organisational Support were used for data collection. Data analysis was performed using descriptive and interpretive statistics (Pearson correlation coefficient test and linear regression). Results: The mean [Standard Deviation (SD)] resilience score was 65.86 (14.01). In addition, the mean (SD) scores of organizational support and social support were 21.57 (4.46) and 65.10 (10.93), respectively. The Pearson correlation coefficient test results showed a statistically significant direct relationship between social support and resilience (r = 0.41, p < 0.001). In addition, there was a statistically significant relationship between organizational support and resilience (r = 0.16, p = 0.01). Multivariate linear regression analysis showed that for each unit increase in social support and organizational support scores, resilience scores increased by 0.41 (p = 0.01) and 0.15 (p < 0.001) units, respectively. Conclusions: The results of the present study showed a direct relationship between resilience and social support and organizational support in nurses. Due to the prolongation of the COVID-19 pandemic and the high prevalence of the disease in our country, nursing managers should seriously consider measures to protect their staff.